Consumer Protection Againts Innappropriate Online Goods Purchases Reviewed From The Civil Code and Consumer Protection Law - Turnip, Johannes Mangapul; Amalia, Apri (Journal of Law Science, 2024)
Online buying and selling transactions are carried out by some Indonesian people through e-commerce platform whice are a technological development. Online purchasing transactions are carried out to save time and make things easier for buyers. However, there is a phenomenon in online purchases in the form of consumer complaints regarding dissatisfaction with the goods purchased which do not match  the information provided by the seller. The identification of the research problem is how consume law is protected in the civil code and consumer protection law and the responsibility of business actors for consumer losses. The aim of the research is to determine consumer legal protection and the responsibilities of business actors towards consumers. The research uses normative juridical research, a statutory regulation approach and is analysed qualitatively. Consumer protection is regulated in the civil code and consumer protection law number 8 of 1999 which regulates the protection and replacement of goods if the goods received by the consumer do not conform to what was agreed in the sale and purchase transaction. The responbility of business actors for consumer losses is to provide compensation for demage, replacement of goods and/or refunds